Fetal anomalies associated with HNF1B mutations: report of 20 autopsy cases4. (6th July 2016) - Duval, Hélène; Michel‐Calemard, Laurence; Gonzales, Marie; Loget, Philippe; Beneteau, Claire; Buenerd, Annie; Joubert, Madeleine; Denis‐Musquer, Marielee; Clemenson, Alix; Chesnais, Anne‐Laure; Blesson, Sophie; De Pinieux, Isabelle; et al.
Abstract: Objectives: To describe macroscopic and microscopic anomalies present in fetuses carrying hepatocyte nuclear factor‐1 β mutation, their frequency, and genotype/phenotype correlations. Methods: Clinical data, ultrasound findings, genetic studies, and autopsy reports of 20 fetal autopsies were analyzed. Histology was reviewed by two pathologists. Results: Macroscopic findings were typically unilateral or bilateral renal enlargement and cortical cysts. Renal lesions were associated with congenital anomalies of the kidney and urinary tract in 25% of cases. Microscopic renal anomalies were dominated by glomerulocystic kidney and renal dysplasia. Extra‐renal manifestations such as pancreatic hypoplasia (75%) and genital anomalies (68%) were only detected at autopsy. In 40% of cases, there was heterozygous deletion of the whole gene. There were de novo mutations in 40%. Conclusion: This study underlines the importance of considering hepatocyte nuclear factor‐1 β mutations in fetuses with congenital anomalies of the kidney and urinary tract, especially when associated with pancreatic hypoplasia. No correlation between phenotype and genotype was found, highlighting high intra‐familial variability in cases with inherited mutations. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known about this Topic? Hepatocyte nuclear factor‐1 β mutations are associated with congenital anomalies of the kidney and urinary tract, pancreatic hypoplasia, and genital malformations but few data about frequency and microscopic anomalies in fetuses. What does this Study Add? Our retrospective study of 20 fetal autopsies, the largest fetal cohort to date, describes all macroscopic and microscopic abnormalities encountered in this syndrome – their frequency. It also discusses genotype/?phenotype correlations and makes a comparison to literature data.